MASH Suite: A User-Friendly and Versatile Software Interface for High-Resolution Mass Spectrometry Data Interpretation and Visualization - Guner, Huseyin (2014)
The rapid advancements in mass spectrometry (MS) instrumentation, particularly in Fourier transform (FT) MS, have made the acquisition of high-resolution and high-accuracy mass measurements routine. However, the software tools for the interpretation of high-resolution MS data are underdeveloped. Although several algorithms for the automatic processing of high-resolution MS data are available, there is still an urgent need for a user-friendly interface with functions that allow users to visualize and validate the computational output. Therefore, we have developed MASH Suite, a user-friendly and versatile software interface for processing high-resolution MS data. MASH Suite contains a wide range of features that allow users to easily navigate through data analysis, visualize complex high-resolution MS data and manually validate automatically processed results. Furthermore, it provides easy, fast and reliable interpretation of top-down, middle-down and bottom-up MS data. MASH Suite is convenient, easily operated and freely available. It can greatly facilitate the comprehensive interpretation and validation of high-resolution MS data with high accuracy and reliability.